Analysis of spatiotemporal variability in temperature extremes in the Yellow and Yangtze River basins during 1961–2014 based on high‐density gauge observations. (30th June 2019) - Niu, Zigeng; Wang, Lunche; Fang, Lulu; Li, Jiarui; Yao, Rui
Abstract: The Yellow and Yangtze River basins are the most important basins in China due to their environment and natural and socioeconomic conditions, and they are highly sensitive to extreme climate events. In this study, we used daily maximum and minimum temperature data gathered from 892 meteorological stations to analyse the spatiotemporal variations in temperature extremes in the Yellow and Yangtze River basins during 1961–2014 and identified correlations with the geographic location and atmospheric circulation patterns. The results indicated that annual mean maximum and minimum temperatures ( TX m and TN m ), most warm extremes and some cold extremes (minimum of the minimum temperature and maximum temperature, TN n and TX n ) generally showed low values in the northwestern region of the Yellow and Yangtze basins, while the diurnal temperature range (DTR) and some cold extremes (ice days, ID 0 and frost days, FD 0 ) were generally higher in the northwest of the two basins. TX m, TN m, all warm extremes and some cold extremes ( TN n and TX n ) showed significant increasing trends in both basins. The increase in the extreme temperature was between 0.17–0.38°C/decade in the Yellow basin, while the interval was 0.15–0.38°C/decade in the Yangtze basin. DTR decreased by −0.07 days/decade in the former and −0.05 days/decade in the latter. Furthermore, warm event days increased by 1.38–3.52 and 1.42–2.65 days/decade in the Yellow and Yangtze basins, respectively. At the same time, the cold event days decreased by −1.90 to −3.47 and −0.20 to −2.70 days/decade in the respective basins. In terms of the spatial patterns, most stations that displayed significant trends were located over the Loess Plateau in the Yellow River basins; Sichuan basin and the lower reaches of the Yangtze River basins. Moreover, almost all of the temperature extremes exhibited the largest trends in spring and winter in the two basins. Most temperature extremes showed strong correlations with longitude and altitude and the Atlantic Multidecadal Oscillation (AMO) displayed significant correlations with almost all of the temperature extremes, except DTR, TN n and TX n ; the East Atlantic/Western Russia (EA/WR) was also related to many temperature extremes. Finally, most temperature observations showed abrupt changes in the 1990s, and the timing in the Yangtze River basin was generally later than that in the Yellow River basin. Abstract : Location of study area and spatial distribution of meteorological stations.